A Comparative Analysis of the Effect of Migration and Foreign Direct Investment on Trade in the Context of the Factor Mobility - Hande Aksöz Yılmaz (Sosyal Siyaset Konferansları Dergisi)
This study investigates the effect of immigration and foreign direct investment on trade within the framework of factor mobility. Hence, we used annual data, spanning the period of 2000–2018, and immigration flows to Turkey’s major trade partners (Germany, France, Italy, UK, and the United States). The inward foreign direct investment flows to Turkey from these countries. However, exchange rates, foreign employment, globalization index, and political stability index variables affect trade. The findings show that migration flows from Turkey to five countries and have more impact on trade, compared to inward foreign direct investment to Turkey overthe period of 2000–2018. Furthermore, when the fundamental assumptions of traditional foreign trade theories are ignored, parallel results are obtained, indicating that factor movements and trade are complementary.